Assessment of prurigo of pregnancy in patients without atopic background - Flavia Naranjo Ravelli, MD; Mohamad Goldust, MD; George Kroumpouzos, MD, PhD (Wolters Kluwer, 2020)
Background: Prurigo of pregnancy (PP), a specific pregnancy dermatosis, has been associated with atopic background in the patient and/or the patient's family. However, this association was not validated in some studies, and cases without atopic background have been reported. Objective: This study aimed to evaluate the clinical features of PP not related to atopic background and search for comorbid conditions in medical and obstetric records. Methods: In this case series, patients with typical PP presentation (i.e., pruritic, discrete papulonodules on the extensor surfaces of the extremities) diagnosed at the dermatology clinics of tertiary referral hospitals were evaluated. The exclusion criteria included missing historical data, inadequate follow-up, laboratory test results suggestive of other pruritic conditions, history of atopic disease, and family history of atopy. Clinical and laboratory data including course, response to treatment, serum total immunoglobulin E level, and comorbidities in the medical and obstetric history were collected. Results: Twenty patients developed PP predominantly during the late second or early third trimester. Nine patients reported that itching developed first, versus 10 patients who reported that lesions started first (one patient was uncertain about onset). There was no recurrence postpartum (mean postpartum follow-up, 17 months). Serum total immunoglobulin E level was elevated in 3 of 14 patients tested (21.4%). Obstetric history (n = 12) included polymorphic eruption of pregnancy (16.6%), PP (16.6%), and gestational pruritus (8.3%). Two of 20 patients (10%) had a history of pruritic skin condition (prurigo nodularis and pruritus of unclear etiology) while not pregnant. Medical history (n = 20) included psychiatric disease (20%) (obsessive compulsive disorder and anxiety), hypothyroidism (10%), and obesity (10%). Conclusion: PP can develop in patients without an atopic background. This finding should be considered when classifying specific pregnancy dermatoses. A thorough medical and family history with a focus on atopy should be obtained from every patient with a gestational eruption, and patients should be counseled accordingly.